Mango kernel oil as a cocoa butter equivalent - Salvador, Nina Lorena Dizon; Dumelod, Benelyn Domingo (1997.)
Mango kernel oil was extracted by solvent extraction obtaining a yield of 6.5%. Its physico-chemical properties were determined, then compared with those of cocoa butter. Results showed that the properties of mango kernel oil and cocoa butter were similar. The crude oil was refined by degumming, neutralization, bleaching and deodorization. The refined oil was made into a molded chocolate product. Three batches of chocolate products were made, one with 100% cocoa butter (Batch 1), another using 100% mango kernel oil (Batch 2) and the last using 50-50 mixture of mango kernel oil and cocoa butter (Batch 3) as raw material. Batch 2 and 3 were compared with Batch 1. Results of the sensory analysis showed that there is a significant difference between the chocolate products using 100% mango kernel oil and 100% cocoa butter. However, the results also showed that there was no significant difference between the chocolate products using 50-50 mixture of mango kernel oil-cocoa butter with tat using 100% cocoa butter.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Mango; Oils and fats; Cocoa butter